The Plot Against America - Roth, Philip (Boston : Houghton Mifflin, 2004)
In a novel of alternative history, aviation hero Charles A. Lindbergh defeats Franklin Roosevelt in the 1940 presidential election, negotiating an accord with Adolf Hitler and accepting his conquest of Europe and anti-Semitic policies.
June 1940-October 1940: Vote for Lindbergh or vote for war -- November 1940-June 1941: Loudmouth Jew -- June 1941-December 1941: Following Christians -- January 1942-February 1942: Stump -- March 1942-June 1942: Never before -- May 1942-June 1942: Their Country -- June 1942-October 1942: Winchell riots -- October 1942: Bad days -- October 1942: Perpetual fear -- Postscript: Note to the reader -- True chronology of the major figures -- Other historical figures in the work -- Some documentation.
new book 2024 summer.
1640L
Accelerated Reader
Keywords: Lindbergh, Charles A. -- 1902-1974 -- Fiction; Presidents -- United States -- Fiction; Presidents -- Election -- Fiction; Jews -- United States -- Fiction; Jewish families -- Fiction; Antisemitism -- Fiction; Political fiction; Newark (N.Y.) -- Fiction; Alternative histories (Fiction); Political fiction; Jewish fiction